Testicular subcutaneous allografting followed by immunosuppressive treatment promotes maintenance of spermatogonial cells in rainbow trout (Oncorhynchus mykiss) - Yoshinaga, Tulio Teruo (2021)
Germ cell transplantation and testis graft represent promising biotechnologies that can be applied for the reproduction of commercial or endangered species. However, mechanisms of rejection from the host immune system might remove the transplanted donor cells/tissues and limit the surrogate production of gametes. In this work, we administered emulsion containing-immunosuppressants to verify whether they are capable to prevent immune rejection and promote survival of testis allografts in rainbow trout. In the first part of this study, we demonstrated in vitro that tacrolimus and cyclosporine were able to affect viability, inhibit leucocyte proliferation, and suppress il2 expression in vitro. In in vivo experiments, both doses of tacrolimus (0.5 and 1.5 mg/kg) and the lower dose of cyclosporine (20 mg/kg) significantly inhibited the expression of il2 in head kidney, three days post-injection. A higher dose of cyclosporine (40 mg/kg) was able to inhibit il2 expression for up to seven days post-injection. In the second part, testis allografts were conducted in fish treated weekly with emulsion containing-tacrolimus. Immunohistochemical, conventional histology, and qRT-PCR (vasa) analysis demonstrated the presence of spermatogonial cells by the fifth week, in animals treated with 0.5 mg/kg of tacrolimus similar as found in autografted group. In the group treated with the highest tacrolimus dose (1.5 mg/kg) and in the non-treated group (without immunosuppressant), no germ cells or their respective markers were detected. il2 expression in head kidney was also suppressed in grafted animals treated with tacrolimus compared to nontreated group. These results suggest that tacrolimus may be a promising immunosuppressant for testis allografts or germ cell transplantation in rainbow trout. Co-administration combining tacrolimus (at lower dose) with other immunosuppressive drugs for inhibiting other activation pathways of the immune system, as performed in human organ transplantation, could be an alternative approach to optimize the immunosuppressive effects in host organisms.